The Influence of Selling Capability on Moderate Firm Value Relative Strategic Emphasis, Market Volatility and Technology Volatility - Valeria Natasha; Kim Sung Suk (SEAN Institute, 2026)
The company's ability to create sales and strategies to create selling value to consumers are factors that investors pay attention to so that they can influence the value of the company. This research aims to examine the influence of selling capability on firm value which is moderated by relative strategic emphasis, market volatility and technology volatility. Research was conducted on all companies that had IPOs in Indonesia in the 2014-2023 period. The analysis was carried out quantitatively using panel data regression analysis techniques using Stata, as well as data envelopment analysis (DEA) in measuring the selling capability variable. The research results show that selling capability does not significantly influence firm value, apart from that relative strategic emphasis and technology volatility are also unable to moderate the influence of selling capability on firm value. However, market volatility can significantly moderate the influence of selling capability on firm value.